2009
DOI: 10.1007/s10295-009-0596-x
|View full text |Cite
|
Sign up to set email alerts
|

Optimized lipase-catalyzed synthesis of adipate ester in a solvent-free system

Abstract: Immobilized Candida antarctica lipase-catalyzed esterification of adipic acid and oleyl alcohol was investigated in a solvent-free system (SFS). Optimum conditions for adipate ester synthesis in a stirred-tank reactor were determined by the response surface methodology (RSM) approach with respect to important reaction parameters including time, temperature, agitation speed, and amount of enzyme. A high conversion yield was achieved using low enzyme amounts of 2.5% w/w at 60 degrees C, reaction time of 438 min,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 21 publications
(30 reference statements)
1
27
0
1
Order By: Relevance
“…The F-MWCNTs allowed for a robust setting for the CRL enzyme linkage [32,44] and improved the hydrophobicity of the microenvironment. [45,46] Nonetheless, the concentration of the formed ester declined at temperatures exceeding 50 C, which was probably caused by the partial inactivation of the CRLMWCNTs. This outcome was somewhat anticipated as the reaction temperature (T > 50 C) had exceeded the optimal temperature of the enzyme.…”
Section: Rsm Experiments and Model Fittingmentioning
confidence: 99%
See 1 more Smart Citation
“…The F-MWCNTs allowed for a robust setting for the CRL enzyme linkage [32,44] and improved the hydrophobicity of the microenvironment. [45,46] Nonetheless, the concentration of the formed ester declined at temperatures exceeding 50 C, which was probably caused by the partial inactivation of the CRLMWCNTs. This outcome was somewhat anticipated as the reaction temperature (T > 50 C) had exceeded the optimal temperature of the enzyme.…”
Section: Rsm Experiments and Model Fittingmentioning
confidence: 99%
“…Higher reaction temperatures tend to promote propensity of enzyme inactivation, due to conformational changes in the enzyme tertiary structure. [45,46] The study found that by increasing the reaction temperature up to 56 C, higher yields of methyl oleate were possible, albeit by also increasing the reaction time. From an economic point of view, it is more desirable for the esterification process to be executed at a much lower reaction temperature, because less energy is required to operate the large bioreactors.…”
Section: Rsm Experiments and Model Fittingmentioning
confidence: 99%
“…[18] It is pertinent to highlight that the presence of excess alcohol molecules in an enzyme-catalysed esterification reaction is predisposed to promote distortion of the essential water layer from the enzyme molecules. [16] Effect of temperature and solvent log P Figure 4 illustrates the effect of varying temperature and solvent log P on the esterification production of geranyl propionate at constant conditions of 6 h and a geraniol:propionic acid molar ratio of 3:1. The highest conversion of geranyl propionate of 46.39% was obtained at 52 C in solvent log P » 3.0.…”
Section: Resultsmentioning
confidence: 99%
“…[9] In fact, the complexity of the enzyme-catalysed reactions can be enhanced by the sensitivity of the enzyme structure to variables, such as temperature, reaction time, substrate molar ratio and activator or inhibitor concentrations. [9,16] This is the reason why research studies often resort to utilizing a statistical tool known as response surface methodology (RSM). [17] This method uses multiple variables to establish optimum conditions under predetermined reaction preferences, such as high product yield at the lowest cost and/or with the least number of experiments.…”
Section: Introductionmentioning
confidence: 99%
“…Since the choice of organic solvents based on minimization of acyl migration may conlict with maximization of transesteriication, acyl migration is usually minimized by reducing reaction times [85]. With increasing concern for the environment, synthesis of PL in solvent-free systems [86][87][88] and ionic liquids systems [89] has been extensively studied. The enzymatic synthesis of vanillyl-PUFA esters from ish oil and vanillyl alcohol in acetone solvent medium was studied by [10].…”
Section: Enzyme Reactions In Organic Solvent Media (Osm)mentioning
confidence: 99%